Three Dimensional Animation of How to Breed Rabbit - Tri Listyorini; Syaifur Rochman; Rizkysari Meimaharani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Rabbit is one of the animal groups that is included in herbivore livestock that has been known by people beside of goat, cow, buffalo etc. Most countries in this world have rabbit livestock because of the rabbit has a high body adaptation energy that can make them live in most of the world. Some of the advantages of rabbit breeding are from the side of economic profits. Because of that, this research presents an animation of the way to breed rabbit well and correctly, because rabbit breeding is one of the benificial activities or hobbies. Through media information which uses animation, the process of information delivery will be easier to understand rather than using oral or written from. Therefore, how to breed rabbit animation will make people know the way to breed rabbit well and correctly, that will serve as a three-dimensional form.